Improving the OSH Knowledge of Indonesian Forestry Workers by Using Safety Game Application: Tree Felling Supervisors and Operators - Efi Yuliati Yovi; Yozo Yamada; Mohammad Faiz Zaini; Chika Annisa Yonanda Kusumadewi; Lerfi Marisiana (Institut Pertanian Bogor (IPB University), 2016)
This research focused on the possibility to improve the possession of OSH knowledge of Indonesian forestry workers, especially of both supervisor and operators who carried heavy responsibilities as executors of any forestry program. To meet the demand of both respondent groups, a prototype of a board - education game developed in 2015 called